Developing climate‐resilient crops: improving plant tolerance to stress combination. (22nd September 2021) - Rivero, Rosa M.; Mittler, Ron; Blumwald, Eduardo; Zandalinas, Sara I.
SUMMARY: Global warming and climate change are driving an alarming increase in the frequency and intensity of different abiotic stresses, such as droughts, heat waves, cold snaps, and flooding, negatively affecting crop yields and causing food shortages. Climate change is also altering the composition and behavior of different insect and pathogen populations adding to yield losses worldwide. Additional constraints to agriculture are caused by the increasing amounts of human‐generated pollutants, as well as the negative impact of climate change on soil microbiomes. Although in the laboratory, we are trained to study the impact of individual stress conditions on plants, in the field many stresses, pollutants, and pests could simultaneously or sequentially affect plants, causing conditions of stress combination. Because climate change is expected to increase the frequency and intensity of such stress combination events (e.g., heat waves combined with drought, flooding, or other abiotic stresses, pollutants, and/or pathogens), a concentrated effort is needed to study how stress combination is affecting crops. This need is particularly critical, as many studies have shown that the response of plants to stress combination is unique and cannot be predicted from simply studying each of the different stresses that are part of the stress combination. Strategies to enhance crop tolerance to a particular stress may therefore fail to enhance tolerance to this specific stress, when combined with other factors. Here we review recent studies of stress combinations in different plants and propose new approaches and avenues for the development of stress combination‐ and climate change‐resilient crops. Significance Statement: Climate change and global warming increase the likelihood that trees and crop plants will be subjected to a combination of different abiotic and biotic stresses, compromising global food production and security. This paper reviews recent advances in the study of plant responses to stress combinations and proposes potential strategies to develop crops with high resilience to a wide range of stress factors and their combination.